Service Users' Perspectives on the Implementation of a Psychoeducation Group for People on the Waiting List of a Specialist ADHD Service: A Pilot Study. - Gore, Bethany; Omoni, Frederick; Babiker, Jemma; Painter, Jon (Nursing Reports, 2023)
In the UK, Attention Deficit Hyperactivity Disorder and waits for assessment, diagnosis, and treatment are all growing problems. This study set out to gather service users' suggestions as to how one specialist ADHD service could improve the experiences of people on their waiting list. Following a semi-structured focus group, an inductive thematic analysis of data yielded three themes: (1) support for psychoeducation in principle, (2) psychoeducation regarding the wider, holistic impact of ADHD, and (3) suggested structures and approaches, as well as (4) a set of general feedback that could inform service developments. Service users supported the notion of psychoeducation sessions to inform people on the waiting list about the wide range of potential impacts of ADHD, the most common psychiatric comorbidities, some potential coping strategies they could try, and the service they could ultimately expect to receive. Some form of one-to-one telephone support was also advocated, primarily to address their concerns about the lack of individualisation group psychoeducation could offer. The potential benefits of these suggestions combined with the low risk of adverse effects makes group psychoeducation a worthwhile waiting list initiative. However, as with any service development, it should be piloted and evaluated before being termed treatment as usual for the service.